ASSISTÊNCIA DE ENFERMAGEM A PACIENTE DEPENDENTE DE DROGAS - Maguida Costa Stefanelli; Ilza Marlene Kuae Fukuda; Evalda Cançado Arantes
The authors describe types of drug addiction, behavior of the drug addict patient and the role of nursing personnel in dealing with them. They also mention some prophylactic measures in the fight off drug addiction.